ISU GENDER DALAM PENDIDIKAN ISLAM - Mardliyah, Mardliyah (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
Islamic education is a process in forming human being totally, and without to differentiate between men and women. The existing of discrimination and the forms of injustice of gender is the influence from the local culture and also from interpreting method of Al-Qur’an verses that is less for women side. This is because Al-Qur’an verses was understood partially and uncontectually. The Solution to overcome that problem is by understanding Al-Qur’an verses and Hadits Nabi/Prophet proportionally and giving opportunity to the women for getting better education.